1974
DOI: 10.1063/1.1686585
|View full text |Cite
|
Sign up to set email alerts
|

An x-ray spectral measurement system for nanosecond plasmas

Abstract: A 15-channel Ross filter/silicon diode detection system has been developed for measuring nanosecond pulsed x-ray spectra in the energy range from 4.5 to 116 keV. The theory and practical aspects of Ross filters and silicon diode detectors are discussed as applied to this system. The data read-out system consists of a current integrator array, a simultaneous multichannel digital voltmeter, and oscilloscopes. The system is designed for compatibility with a small computer to allow real time spectral measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Figure 1 illustrates five response functions, used in this article, that define several superposed regions of x-ray sensitivity (or, so-called, ''spectral cuts'') between 100 eV and 5 keV. Similarly shaped responses have been reported for a variety of detectors combined as simple arrays with upstream filters and in differing spectral ranges [40][41][42][43][44][45]. Improvements to this basic design for soft x rays have been achieved by inserting additional x-ray components, upstream of the detectors [46][47][48].…”
Section: Introductionmentioning
confidence: 94%
“…Figure 1 illustrates five response functions, used in this article, that define several superposed regions of x-ray sensitivity (or, so-called, ''spectral cuts'') between 100 eV and 5 keV. Similarly shaped responses have been reported for a variety of detectors combined as simple arrays with upstream filters and in differing spectral ranges [40][41][42][43][44][45]. Improvements to this basic design for soft x rays have been achieved by inserting additional x-ray components, upstream of the detectors [46][47][48].…”
Section: Introductionmentioning
confidence: 94%
“…1. A simple method using a set of filters along with PINdiode detectors was conducted [26] to analyze the energy spectrum of the X-rays. The filters included Cu (15 µm show transmission curves of the filters and the detectors' responses, respectively.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…The study also includes an analysis of the energy spectrum of multi-radiation of X-rays together with its contribution during the radiation process, using a four-channel diode X-ray spectrometer (DXS) and suitable X-ray filters. [26]…”
Section: Introductionmentioning
confidence: 99%
“…An important part of the recent experimental studies on x-ray and particle emission from PF is oriented in interesting applications such as contact microscopy, x-ray and electron beam lithography, generation of soft x-ray spectral lines of highly charged heavy metal ions, metal coating by ion sputtering, surface modification and deposition of thin films, x-ray backlighting, radiography of biological and mechanical objects, and micromachining. [8][9][10][11][12][13][14][15][16] The x-ray emission from a given PF device depends in a rather complicated way upon the design and operating parameters such as the operating voltage and bank energy, [17][18][19] the circuit inductance, 20 the working gas nature and pressure, 12,16,21 the anode dimensions, shape, and material, [22][23][24][25][26][27] the material and configuration of insulator sleeve, 28 and preionization assisted breakdown. 29,30 It is reported that when the plasma focus is operated in hydrogen with small admixture of inert gases, the x-ray emission is strongly enhanced.…”
Section: Introductionmentioning
confidence: 99%